Brazil Recognizes the Right to Self-Determination for African Descendants: Is It a Path the United States Could Follow? - Needleman, Ruth (Social justice, 2016)
Brazil and the United States had the largest slave populations in the hemisphere, and, as a result, comparable institutionalized racism and inequalities. At least until the recent "congressional coup" and move to impeach President Dilma Rousseff, Brazil had taken major steps to face its heritage of genocide. Under the Workers' Party governments (2003-2014), Brazil has adopted national quota systems and antipoverty programs aimed at reducing inequality and opening opportunities for education, health care, and housing. In addition, geography, history and culture led to very different migration patterns for African descendants in Brazil, where thousands of black fugitive slave communities (quilombos) arose, and still exist. They have now won rights to their historic lands, giving them autonomy and the right to self-determination. How can cities like Ferguson or Detroit learn from Brazil?